Arsenic resistance and accumulation by two bacteria isolated from Ratanpur Village of Varanasi District, Uttar Pradesh - Kushwaha R.; Singh R.S.; Mohan D. (My University, 2025)
Arsenic-resistant bacteria were isolated from Ratanpur Village of Varanasi District, Uttar Pradesh, by enrichment technique. The isolates, Proteus alimentorum strain TY6 and Pseudomonas aeruginosa strain K7Pb, showed high resistance to As(V) with minimum inhibitory concentration of 610 mM and 350 mM, respectively, and for As(III), 10 mM and 8 mM, respectively. TY6 could remove 96 ± 0.816 % As(V) and 66 ± 0.471 % As(III), whereas K7Pb could remove 98 ± 0.942 % As(V) and 78 ± 1.247 % As(III). Biotransformation ability was determined using AgNO3 and KMnO4 tests. PCR amplification showed the presence of aio, arr, arx and ars genes. Strains also showed resistance against other heavy metals such as Cd, Cr, Co, Pb, Hg, and Ni. Phytotoxicity assessment on chickpea and Vigna radiata (mung bean) revealed that the arsenic-contaminated water treated with the isolates can be used for irrigation purposes. It is also the first report of arsenic remediation by Proteus alimentorum bacteria (to the best of the authors' knowledge). © 2023 Elsevier Ltd